Before the wedding bells : preparing for a lasting & fulfilling marriage - George, Sam; George, Mary (Hyderabad. Good Shepherd Books., 2019)
Amidst the excitement and busyness of planning for a perfect wedding, couples often overlook the more important aspect of preparing for the marriage. Remember, wedding is an event and marriage is lifetime journey! Whether you are having an arranged marriage or love marriage, Before the Wedding Bells is a practical and fun resource to help you prepare for a strong and fulfilling marriage relationship. Whether you hail from the same culture and background or different, here is relational wisdom and fun projects that will prepare you as a couple for gratifying marriage. Are you ready for the adventure of marriage? Be prepared; do not leave anything to chances. Publisher's description
Keywords: Marriage.-- Counseling; Premarital Counseling; Marriage.-- Religious aspects.-- Christianity; Christian Marriage.-- Counseling